Capital Budgeting Practices in Financial Institutions (FIs): An Empirical Study in the Case of Ethiopia - Kesto, Dakito Alemu; Ravi, Jaladi (Global Disclosure of Economics and Business, 2017)
Capital budgeting is the process that requires planning for setting up budgets on projects expected to have long-term  implications,  which  is  used  as  a  standard  for  decision  making  for  any organization. This study attempts to explore the capital budgeting practices in FIs and to ascertain if they had guidelines for capital budgeting techniques. The finding shows that, even if the firms in the sector have made significant investment on long-term assets only 42.9% of the firms were properly practiced the modern approaches of investment evaluation methods. Moreover, the most commonly used long-term investment evaluation techniques were PBP, NPV and IRR respectively. On the other hand, except one firm, which conducts partial analysis about the feasibility, almost all other firms in the sector did not make detail evaluation about the feasibility of investment while opening new branches which similar to study conducted by Eyob Dagne (2010). Similarly, the study also found negligence on the application of cost of capital as most firms were found using the cost of debt while discounting their cash flows despite the fact that most firms were found financing their projects using both debt and equity. In a similar vein, less than 30% of firms in the sector, of those apply capital budgeting techniques while evaluating long-term assets, used risk evaluation approaches. On top of this, inflation is also an area where firms have not paid much attention in their capital budgeting decision making. The study concluded by opening area for further research on how capital budgeting could be used for efficient resource allocation in the process of budgeting in developing countries.